An Analysis of Students’ Difficulties in Writing Descriptive Texts in the Tenth Grade of SMA Kristen Palangka Raya - Marsaleno Agustin; Maida Norahmi; Natalina Asi (General English Education, 2022)
Most students had problems writing a descriptive text when they were assigned their text. Many students were not able to describe themselves or they had difficulties in writing descriptive text. Some students think that writing is the most difficult skill in English. Some students also could not finish their writing at the end of the time set due to limited ideas and vocabulary. This research aimed to describe the students’ difficulties in writing descriptive texts and find out the causes underlining those frequent difficulties. This research uses the qualitative descriptive method. The research subjects were X MIPA students of SMA Kristen Palangka Raya who had difficulties when writing descriptive text. This research involved 17 students as the research subjects. The data of this research were the results of students’ worksheets and the student's answers to the given questionnaires. The researcher employed a writing test and questionnaires to gain descriptive data. As a result, the factors that cause the students’ difficulties in writing descriptive text were students’ lack of vocabulary, difficulties to translate, and lack of competence in understanding English tenses.